A new frontier in biology: deciphering the molecular language of symbiosis - McFall-Ngai, Margaret (Henry Stewart Talks, 2011)
Human organ systems interacting with bacteria, Intestine: 8 divisions, 800 species, 7000 strains, How critical are the microbiota to the overall biology of the host animal?, Conceptual and technical impediments, Impact on the immune system, Genes associated with human genetic disease, The squid-vibrio light organ symbiosis, Microbe Associated Molecular Patterns, Colonization of host tissues and development of the symbiosis, Symbiont induction of host tissue development, Daily rhythms of symbiont associated tissues
Archived at 2016/06/22